Discourses regarding construction of youth identity in Latin America. Political, educational and cultural phenomenon. A look from colombia. [Discursos en torno a la construcción de identidad juvenil en America Latina. Fenómeno político, educativo y cultural. Una mirada desde Colombia.] (2019)
This article results from the research project entitled: Analysis of the impact of socio-communicative glocal discourses on the construction of the reference around the concept of Latin American youth identity. Case of Colombia and it´s objective is to discuss our results with regard to supra-national conceptions and practices. This research project explores the idea of a common Latin American youth identity, based on iconic references selected by university students. Its methodological background consists of the work done in 2015 at the Universidad Complutense de Madrid. This methodology was implemented, with some variations between 2016 and 2017 in Colombia and Argentina. For the Colombian case, participatory tools were used through a seedbed of research with communication students from Universidad de Medellin. The partial results were triangulated with data collected in surveys and discussion groups. The final results suggest the follow-up of supranational agendas embedded in media and educational discourses. Copyright © 2019 (Johana Barreneche-Corrales, Maria-Cristina Pinto-Arboleda, Beatriz-Eugenia Quiceno-Castañeda).